Zer - oo7 Oral health knowledge among Brazilian preschoolers and their carers receiving and not receiving health promotion - Araújo, Paula Caetano; Vettore, Mario Vianna; Baker, Sarah R; Garbin, Clea Adas Saliba; Moimaz, Suzely Adas Saliba; Arcieri, Renato Moreira (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Background. Few studies have evaluated oral health promotion (OHP) programs in nursery schools. This research aimed to assess whether there were differences in oral health knowledge between preschoolers and carers who received or did not receive an OHP program in nursery schools. Methods. A post-intervention observational study involving 5-6 years-old preschoolers and 169 carers was carried out in 10 nursery schools. The preschoolers in the OHP program group (N=93) received information on oral health and recreational activities relating to oral health, whereas in the control group (N=90), no OHP activity was provided. Children’s age and sex, carer’s age, child kinship, education and family income were collected via questionnaire. Children and carer’s oral health knowledge scores were assessed through structured interviews. Independent variables were compared between groups by t-test, Chi-square and Mann-whitney test. The association between children and carer’s oral health knowledge and the OHP program group was tested using multivariate Poisson regression. Results. Children’s oral health knowledge was significantly associated with the OHP program group. Carer’s oral health knowledge did not differ between intervention and control groups. Conclusions. Children attending nursery schools provided with OHP programs had greater oral health knowledge than those attending nursery schools without OHP activities. Descriptors: Health Promotion; Oral Health; Child, Preschool.